A constituição territorial e imaginária da Terra Céltica Insular: Grã-Bretanha e Irlanda - Pastre, Lucas Landim Castroviejo (Universidade Federal de São Carlos, 2016)
Conceptually characterized by linguistic specificity, the Celts were the Indo-European peoples that originated in the northern Alps, possibly even in the middle of the Bronze Age - the result of a long process of prehistoric miscegenations. At the height of their appropriation, they extended over a territorial arc that stretched from Ireland to present-day Turkey, dominating a space of significant significance between Europe and Asia Minor. This is where the Celtic Land emerged, composed of two distinct occupation plots - the continental and the insular. The latter, in turn, endowed itself with peculiarities arising from the geography inherent to its territory, as well as its more recent history, largely associated with the myths that were born of it. Taking the ethnic composition of Great Britain and Ireland - as far as Celtic civilization is concerned - as a consequence of the migrations that took place on the continent, the monograph showed, through various cultures, complex material and documentary reports attributed and / or associated with these peoples, the multiple processes of culminating occupations in the constitution of the Insular Celtic Earth. In view of the imaginary dimension contained in such attributes, historical parallels with Gaelic mythology were sought, albeit with many caveats and cautions, taken concurrently with the analysis of the primeval peoples associated with the "Emerald Island", where it was possible to verify, successfully, hypothetical links with the Iberians.
The territorial and imaginary constitution of the Insular Celtic Land: Great Britain and Ireland
Keywords: Celtologia; Território; Cultura; Europa; Ilhas britânicas; Celtology; Territory; British islands; Europe; Culture; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA